Enhancement of Cu (II), Zn (II), Ni (II) and Humic Acid Adsorption in Modified Bentonite - Kanogwan Tohdee (Prince of Songkla University, 2021)
Thesis (Ph.D., Chemical Engineering)--Prince of Songkla University, 2018